Information and Communication Technologies: Scholars´ Uses and Perceptions - Peruzzo, Kátia Maria; Dal Molin, Eliete; Webber, Carine G. (Scientia cum Industria, 2016)
This article presents preliminary results of a study developed at a Public School in order to investigate how information and communication technologies exist in students and professors lives and how it interferes at their academic lives. This survey was prepared with the intention of better understanding the effects that computers and the internet may have towards our educational system, including students, parents and teachers. Inquiring about this context brings data to guide and evaluate the use of emergent technologies in the learning and teaching processes. It allows us to consider technologies connected to our expectations, promoting better quality in Education and contributing to citizens well prepared to deal with future challenges. http://dx.doi.org/10.18226/23185279.v3iss3p93